UPAYA MENINGKATKAN ASPEK MOTORIK KASAR MELALUI KEGIATAN PERMAINAN LOMPAT TALI PADA ANAK USIA 5-6 TAHUN - Winda Roudotul Jannah; Heri Yusuf Muslihin; Anggi Maulana Rizqi (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
This study aims to improve the gross motor skills of children aged 5–6 years through jump rope activities at TK Cahaya Islam, Garut Regency. The method used is Classroom Action Research (CAR) with the Kemmis and McTaggart model, conducted in three cycles. The research subjects were 19 children from group B2. Data were collected through observation and analyzed using descriptive qualitative and quantitative techniques. The results showed that jump rope activities significantly enhanced children's gross motor abilities, especially in terms of balance and agility. Improvements were observed in each cycle, from the initial condition to the third cycle, with the majority of children reaching the "developing as expected" and "very well developed" categories. Therefore, jump rope games are effective strategies to foster gross motor development in early childhood. Keywords: ross motor skills; jump rope game; early childhood